New formulation for producing salmon pâté with reduced sodium content - Nielsen, Tim (RISE Research Institutes of Sweden, 2020)
Reducing consumption of salt, specifically sodium, is one of the most effective ways to improve public health. A novel formulation for producing salmon pâté with reduced sodium content was investigated. Salmon pâtés with three different sodium concentrations were evaluated using microbiological, sensory and chemical analyses. Saltwell®, a natural salt containing a mixture of sodium chloride and potassium chloride, was used for partial substitution of sodium chloride (table salt) alone in the formulation. Replacing 80% of the sodium chloride with Saltwell®, resulted in a 22% reduction in sodium, without affecting microbial activity. A trained sensory panel observed minor differences in three of the twelve sensory attributes that were evaluated (coherent texture, saltiness, canned fish flavor). However, these differences were only weakly significant. Saltwell is a viable alternative to sodium chloride to produce seafood products with reduced sodium content without compromising quality and safety.

The study was a part of the following Horizon 2020 project:
SEAFOODTOMORROW - Nutritious, safe and sustainable seafood for consumers of tomorrow (773400)

Ett minskat intag av natrium är ett effektivt sätt att förbättra folkhälsan. I denna studie producerades laxpaté med olika mängd natrium i formuleringen. Sensoriska, mikrobiologiska och kemiska analyser genomfördes för att säkerställa produktkvaliteten.

Mer information finns på den engeska sidan.

Arbetet var en del av Horizon 2020-projektet SEAFOODTOMORROW - Nutritious, safe and sustainable seafood for consumers of tomorrow (773400).
Ny formulering för att producera laxpaté med reducerat natriuminnehåll
Keywords: salt; salt; health; hälsa; sodium; natrium; seafood; sjömat; HEALTH; HÄLSA; Food Science; Livsmedelsvetenskap